Funding Allocation to Extracurricular Elementary SchoolManagement (A Site Study at Elementary School StateJurang Ombo Magelang) - Widodo, Bambang Nur (2011)
The objectivesof this research are to (1) to describe the allocation of extracurricular activities funds at SDN Jurang Ombo Magelang. (2) to describe the accounting of extracurricular activities fund at SDN Jurang Ombo Magelang. This is qualitative research and use ethnographic design. This research is conducted at SDN Jurang Ombo Magelang. The main subjects of this research are the principal and teachers at SDN Jurang Ombo Magelang. Data collection methods use in-depth interviews, participatory observation, and documentation. Analysis of data used data analysis model arranged in site. The validity test of data used credibility, transferability, conformabilities and dependability. The results of this research are (1). The allocation of extracurricular activities fund at SDN Jurang Ombo is conducted by the principal that involve budget teams, school committees and teachers. Allocation of funds is established by the allocation of funds that have been through the stages of problem identification and consideration. Source of fund extracurricular activities is taken from the state budget, the BOS, SBS, and also community classes. Lack of extracurricular funds is handled by requesting Rp.10.000.00 for every parent. The allocation of extracurricular funds at SDN Jurang Ombo Magelang is tailored to the needs and thawed in 4 stages that is the first quarter until the third quarter. (2) The accounting of extracurricular activities fund at SDN Jurang Ombo Magelang is done well. The fund accounting made by budget and school finance or LPJ. The Accounting of extracurricular fund is created by the Budget Team at the beginning of a new school year for planning the allocation of extracurricular funds, while to report the use of extracurricular activity funds is made once a month. The accounting format is accordance with the instructions of the mayor of Magelang City. It is noted in the books is an extracurricular activity schedules, student attendance and coach of extracurricular, the need for implementation of extracurricular activities, and also the source of funds. The fund accounting is duplicated twice; accounting of extracurricular funds is covered with pink cover that in the first section written the identity of school.